Adventures in art art & craft experiences for 7- to 14-year-olds - Milord, Susan (Williamson Pub., 1990)
Instructions for 100 arts and crafts activities, including printmaking, animal art, portraiture, sculpture, architecture, wearable art, and much more. Provides cultural and historical information for various items and technologies.